Flexural stability analysis of stiffened plates using the finite element method - Panda, Saleema; Barik, Manoranjan (Computer Assisted Methods in Engineering and Science, 2017)
A four-noded stiffened plate element has been developed which has all the advantages and efficiency of an isoparametric element to model arbitrary shaped plates, but without the disadvantage of the shear-locking problem inherent in the isoparametric element. Another unique feature is that the arbitrary placement of the stiffener inside the plate element is without any restriction of its orientation. The boundary conditions have been incorporated in a general manner so as to accommodate the curved as well as the straight-edged boundaries. The element has been used for stability analysis of arbitrary shaped stiffened plates.Novelty: In this work, a plate bending element is proposed, which can model any arbitrary shape as efficiently as an isoparametric element. As it does not include the shear deformation, thin plate problems can be considered without any numerical difficulties as observed in isoparametric elements. This element is generalized to accommodate any arbitrary shapes of the plate geometry. The mesh divisions for plates with irregular boundaries using the finite element method are sometimes difficult. However, this element eliminates such complexities as the mesh divisions are done in the mapped square plate. The stiffener is modeled so that it can be of any shape, dispositions and be arbitrarily placed on the plate.